Insights Into Students’ Experiences and Perceptions of Remote Learning Methods: From the COVID-19 Pandemic to Best Practice for the Future - Nguyen, Trang; Netto, Camila L. M.; Wilkins, Jon F.; Bröker, Pia; Vargas, Elton E.; Sealfon, Carolyn D.; Puthipiroj, Pipob; Li, Katherine S.; Bowler, Jade E.; Hinson, Hailey R.; Pujar, Mithil; Stein, Geneva M. (Frontiers in Education, 2021)
This spring, students across the globe transitioned from in-person classes to remote learning as a result of the COVID-19 Pandemic. This unprecedented change to undergraduate education saw institutions adopting multiple online teaching modalities and instructional platforms. We sought to understand students' experiences with and perspectives on those methods of remote instruction in order to inform pedagogical decisions during the current pandemic and in the future development of online courses and virtual learning experiences. Our survey gathered quantitative and qualitative data regarding students’ experiences with synchronous and asynchronous methods of remote learning and specific pedagogical techniques associated with each. 4,789 undergraduate participants representing institutions across 95 countries were recruited via Instagram. We find that most students prefer synchronous online classes and students whose primary mode of remote instruction has been synchronous report being more engaged and motivated. Our qualitative data show that students miss the social aspects of learning on campus, and it is possible that synchronous learning helps to mitigate some feelings of isolation. Students whose synchronous classes include active-learning techniques (which are inherently more social) report significantly higher levels of engagement, motivation, enjoyment, and satisfaction with instruction. Respondents’ recommendations for changes emphasize increased engagement, interaction, and student participation. We conclude that active-learning methods, which are known to increase motivation, engagement, and learning in traditional classrooms, also have a positive impact in the remote-learning environment. Integrating these elements into online courses will improve the student experience.